Clinical and neurophysiological characteristics of heterozygous NPC1 carriers. Issue 1 (28th June 2019) - Benussi, Alberto; Cotelli, Maria S.; Cantoni, Valentina; Bertasi, Valeria; Turla, Marinella; Dardis, Andrea; Biasizzo, Jessica; Manenti, Rosa; Cotelli, Maria; Padovani, Alessandro; Borroni, Barbara
Abstract: Niemann‐Pick disease type C (NPC) is an uncommon lysosomal storage disorder, which is characterized neuropathologically by cholinergic dysfunction and presents clinically with a broad series of neurological signs and symptoms. NPC is inherited as an autosomal recessive trait, caused by mutations in the NPC1 or NPC2 genes. However, recent reports have raised concerns on heterozygous NPC1 gene mutation carriers, which historically have been considered as clinically unaffected, occasionally presenting with clinical parkinsonian syndromes or dementia. In the present study, we aimed at comprehensively assessing clinical, biochemical, and neurophysiological features in heterozygous NPC1 gene mutation carriers. We assessed cholinergic intracortical circuits with transcranial magnetic stimulation, executive functions and plasma oxysterol levels in two families comprising two monozygotic twins with a homozygous NPC1 p.P888S mutation, four patients with a compound heterozygous p.E451K and p.G992W mutation, 10 heterozygous NPC1 p.P888S carriers, 1 heterozygous NPC1 p.E451K carrier, and 11 noncarrier family members. We observed a significant impairment in cholinergic circuits, evaluated with short‐latency afferent inhibition (SAI), and executive abilities in homozygous/compound heterozygous patients and heterozygous asymptomatic NPC1 carriers, compared to noncarriers. Moreover, we reported a significant correlation between executive functions performances and both plasma oxysterol levels and neurophysiological parameters. These data suggest that heterozygous NPC1 carriers show subclinical deficits in cognition, possibly mediated by an impairment of cholinergic circuits, which in turn may mediate the onset of neurological disorders in a subset of patients.